AN EVALUATION OF THE NATIONAL UNION CATALOGUE OF NATIONAL LIBRARY & DOCUMENTATION CENTRE OF SRI LANKA - Mapapathirane, M.B.K. (Masters Degree in Library & Information Science (MLS)., 2003)
The main purpose of this study was to evaluate the operations and performance of the National Union Catalogue of National Library & Documentation Centre of Sri Lanka in order to identify the underlying problems and to make recommendations for its improvements. This evaluation would help the NL&DC to justify the operation of the NUC project, to know the effectiveness, to diagnose the problems in the project and for the future developments of the NUC. Two types of questionnaires were used to collect data, from the NUC participants and non-participants. Out of the 68 participants in the NUC, 51 libraries had responded to the questionnaire, which was sent for them. Another questionnaire was sent to 50 nonparticipant libraries and out of them 29 libraries had responded. In addition to the above, observations and interviews were used by the researcher to collect data. The survey findings revealed the following. The participation of academic and public libraries was low in NUC and only large public libraries (with large collection size, large cadre size and large budget level) were interested in participation in NUC. But the collection size, cadre size and budget level were not factors, which influenced the participation of special libraries.